Reducing Social Stress in Urban Adolescents with Peer Network Counseling. - Mason, Michael; Zaharakis, Nikola; Sabo, Roy (Journal of Child & Family Studies, 2016)
Increased social stress in the context of peer interactions is associated with multiple negative health outcomes, including substance use. Addressing social stress could provide protective effects for adolescents who are particularly vulnerable to peer-based issues such as loneliness and perceived isolation. Toward this end, we examined the efficacy of a 20-min substance use intervention named peer network counseling to reduce social stress with 119 urban adolescents. Adolescents presenting at primary care clinics were randomized into treatment or control conditions and followed for 6 months. Utilizing a repeated measures general linear model, we examined the effects of peer network counseling while controlling for race, gender, age, depression symptoms, and substance use (alcohol, marijuana). At 6 months the peer network counseling condition decreased social stress compared to controls ( p < 0.05). A linear mixed-effects moderation model revealed that peer network counseling temporarily moderated the effect of alcohol use, but not for marijuana or heavy alcohol use. Peer network counseling seems to reduce social stress, which suppresses alcohol use among peer network counseling participants in the short term. These promising findings appear to support the efficacy of peer network counseling in reducing social stress, which can moderate alcohol use among urban adolescents.